Combustion and mechanical properties of pellets from biomass and industrial waste; Renewable Energy; Vol. 228 - Dorokhov V. V. Vadim Valerjevich; Nyashina G. S. Galina Sergeevna; Romanov D. S. Daniil Sergeevich; Strizhak P. A. Pavel Alexandrovich (2024, 2024)
Title screen